Green Synthesis of Bis(indolyl)methane Derivatives using PEG-400 - Gurrapu, Raju; Poshala, Ramesh; Kuthati, Bhaskar (Asian Journal of Chemistry, 2018)
Polyethylene glycol (PEG-400) has been considered as an effective and eco-friendly solvent cum activator for the one-pot coupling of indole and aldehydes to produce indole derivatives. The reaction was performed under mild conditions and the versatility of one-pot reaction was confirmed.